(3fXQjI GdbQGQGJ GdJLGQjIs - (3GHQGgje CMeO(B, (3eNdhas ((3GdQjGV(B:s (3LGeYI Gdedc SYhO(B,s, 1990)
(3GdbQGQGJ PGJ GdeQMdI GdhGMOI(B- (3TLQI GdbQGQGJ hLOhi GdeYdheGJ GdJLGQjI(B- (3EJNGP GdbQGQGJ hGdeYGjfI aj VhA GdJhRjY GdWHjYj(B- (3eaghe GdefaYI(B- (3GdhUa GdYGe ddefaYI heaghe GdESJQGJjLjI(B- (3GddYHI GdKfGFjI GdUaQjI(B- (3HYV WQb Md GddYHI GdKfGFjI GdUaQjI(B- (3GddYHI GdKfGFjI ZjQ GdUaQjI(B- (3GddYHI GdYGeI GdechfI ef CTNGU YOOge (Bn.s
Keywords: (3EJNGP GdbQGQs; (3GdJLGQI(B- (3JfXje hEOGQIs